Implications of Transcranial Magnetic Stimulation as a Treatment Modality for Tinnitus - Alexa J. Denton (MDPI AG, 2021)
Repetitive transcranial magnetic stimulation (rTMS) is a non-invasive, neuromodulating technique for brain hyperexcitability disorders. The objective of this paper is to discuss the mechanism of action of rTMS as well as to investigate the literature involving the application of rTMS in the treatment of tinnitus. The reviewed aspects of the protocols included baseline evaluation, the total number of sessions, frequency and the total number of stimuli, the location of treatment, and the outcome measures. Even with heterogeneous protocols, most studies utilized validated tinnitus questionnaires as baseline and outcome measures. Low frequency (1 Hz) stimulation throughout 10 consecutive sessions was the most widely used frequency and treatment duration; however, there was no consensus on the total number of stimuli necessary to achieve significant results. The auditory cortex (AC) was the most targeted location, with most studies supporting changes in neural activity with multi-site stimulation to areas in the frontal cortex (FC), particularly the dorsolateral prefrontal cortex (DLPFC). The overall efficacy across most of the reviewed trials reveals positive statistically significant results. Though rTMS has proven to impact neuroplasticity at the microscopic and clinical level, further studies are warranted to demonstrate and support the clinical use of rTMS in tinnitus treatment with a standardized protocol.